Integration of ICT in assessments of large classes : a case of Strathmore University - Mukandutiye, Delphine Bheny (Strathmore University, 2014)
ICT can contribute to the development and efficiency of education management and administration. Efforts to introduce ICT in teaching, learning and assessment aim to help meet a wide variety of goals in the education sector. This dissertation is based on a research project that was driven by challenges facing traditional assessment of large classes, such as time consuming, late feedback among others. The research aimed at studying the widely used e-assessment tools, designing and testing the e-assessment framework and evaluating if differences existed between performances of students examined with traditional assessment and those examined with e-assessment, Furthermore, the research intended to investigate the feasibility of implementing e-assessment to complement eLearning in the University. The researcher used desktop research for relevant literature reviews for the e-assessment practice. Post-surveys were also conducted with over 300 users which included students and academic staff from various faculties in Strathmore University to gather their views on eassessment. Benefits and limitations of e-assessment were discussed. 87% of the respondents preferred eassessment over traditional assessment. It was revealed that e-assessment was better than traditional assessment because students performed better and they were happy about the instant feedback, lecturers spent more time setting up CATs but enjoyed the automated marking, analysis of results was easier and reports generation was faster. The University could also save about Kshs 2,060,800 (USD 24,000) per year by implementing e-assessment. The success of this research resulted to an eLearning Support Centre that was established to spearhead e-assessment, e-feedback and mobile learning in Strathmore University. The Centre aims at bringing about a better learning experience based on successful research.
A dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunication and Innovation (MSc. MTI)
Keywords: ICT; Education; Teaching; Learning; Strathmore University; ICT in education; e-assessment; Moodle; eLearning; assessment of large classes; mlearning; eLearning Support Centre